Conjugation Effects of Styryl Versus Heterocyclic π -Linker on Triphenylamine-based Dyes in Dye-sensitized Solar Cells - Wang, Po-Hsin; Wang, Tzong-Liu; Chang, Pei-Yu; Yang, Chien-Hsin (Current Organic Chemistry, 2017)
Background: Dye-sensitized solar cells have received attention recently for efficient converting sunlight to electricity. Organic dyes provide a feasible alternative due to the practical advantages, such as facile structure tuning, easy synthesis process, and low cost. Organic sensitizers are generally designed to link the electron donor and the electron acceptor. When light irradiated on the dyes, these dipolar molecules induce intramolecular charge transfer from the donor to the acceptor, and the electron is then injected into TiO2 via the anchoring groups (carboxylic acids). Objective and Method: This work systematically synthesized the dyes containing triphenylamine as the electron donor, a series of donor-π-acceptor as the conjugation segment, and 2-cyanoacetic acid as the electron acceptor, where donor-π-acceptor structures are expected to enable efficiently photoinduced charge separation. The photovoltaic performance of the dyes is significantly related to the linker type. Results: The charge transfer from the excited dye molecules to the conduction band of TiO2 is improved in the styrene-π -linked dye, showing highly effective improvement in the efficiency of the corresponding devices as compared dye-based devices with N-methylpyrrole, 3,4-ethylenedioxythiophene linkers and no linker. The device with N-methylpyrrole-linker-based dye bearing positions of C3 and C4 on N-methylpyrrole linker has the lowest conjugation effect and efficiency. Styrene-linker-based dye shows a broad incident-photon-tocurrent conversion efficiency response with a signal of up to 670 nm, covering most of the ultrviolet-visible light region. Conclusion: Device efficiencies of 5.18% and 7.56% for dye-sensitized devices using Styrene-linker-based dye and N3 dye, respectively, assembled using the same method and measured under AM 1.5 irradiation.
Keywords: Dye-sensitized solar cells